2007
DOI: 10.3844/ajptsp.2007.148.158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D- and L-Glucose and Mannitol on Retinal Capillary Cells: Inhibition by Nanomolar Aminoguanidine

Abstract: Hyperglycemia may contribute directly to pericyte loss and capillary leakage in early diabetic retinopathy. To elucidate relative contributions of glycation, glycoxidation, sugar autoxidation, osmotic stress and metabolic effects in glucose-mediated capillary damage, we tested the effects of D-glucose, L-glucose, mannitol and the potentially protective effects of aminoguanidine on cultured bovine retinal capillary pericytes and endothelial cells. Media (containing 5 mM D-glucose) were supplemented to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…To date, we do not know the molecular mechanism leading to decrease in SPP1 in these conditions. Potential effects of hyperglycemia in diabetes range from specific metabolic effects, through non-enzymatic glycation, glycoxidation, lipoxidation and osmotic stress ( Yu et al, 2007 ). In our cell culture environment, mannose was applied to specifically induce osmotic effects in the explants and to distinguish them from the other hyperglycemia-induced mechanisms ( Yu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, we do not know the molecular mechanism leading to decrease in SPP1 in these conditions. Potential effects of hyperglycemia in diabetes range from specific metabolic effects, through non-enzymatic glycation, glycoxidation, lipoxidation and osmotic stress ( Yu et al, 2007 ). In our cell culture environment, mannose was applied to specifically induce osmotic effects in the explants and to distinguish them from the other hyperglycemia-induced mechanisms ( Yu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential effects of hyperglycemia in diabetes range from specific metabolic effects, through non-enzymatic glycation, glycoxidation, lipoxidation and osmotic stress ( Yu et al, 2007 ). In our cell culture environment, mannose was applied to specifically induce osmotic effects in the explants and to distinguish them from the other hyperglycemia-induced mechanisms ( Yu et al, 2007 ). Since the observed effects on the abundance of SPP1 also occurred in the osmose control group, we speculate that alterations in the SPP1 protein levels might result from a multi-causative osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the observed stereoselectivity is in contrast with protein glycation by natural sugars, where reactivity is not dictated by stereochemistry. [25] …”
mentioning
confidence: 99%
“…We recently discovered that RLIP76 knockout mice are entirely deficient in CDE (Singhal et al, 2008b); though this CDE can be fully reconstituted by transfecting wild-type RLIP76 into mouse embryonic fibroblasts, mutants of RLIP76 lacking GS-E bindingor nucleotidase activity fail to reconstitute CDE. RLIP76 also provides defense against oxidative stress by transporting glutathione conjugates of electrophilic lipid peroxidation toxic end-products, e.g., 4-hydroxynonenal, generated during oxidative stress (Awasthi et al, 2008;Mucimapura et al, 2010;Yu et al, 2007). In mammalian cells, RLIP76 accounts for up to 80% transport of glutathione conjugates of drugs and endogenous electrophiles (Awasthi et al, 2003;Singhal et al, 2003) and in human cells it has been shown to be the major determinant of drug resistance (Awasthi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic Cells (DCs), together with monocytes and macrophages constitute the heterogeneous population of mononuclear phagocytic system and act as non-specific effectors against foreign intruders and tumors (Banchereau and Steinman, 1998;Mellman and Steinman, 2001;Steinman and Banchereau, 2007). In their immature state, DCs localized throughout peripheral tissues recognize Pathogen-Associated Molecular Patterns (PAMPs) and, through an array of Pattern-Recognition Receptors (PRRs) capable of binding and internalizing ligands of diverse structures (Janeway, Jr. and Medzhitov, 2002;Yu et al, 2007), channel activation/maturation signals into the cells for their further differentiation. Immature DCs (iDCs), in addition to macropinocytosis and phagocytosis, capture antigens by receptor-mediated endocytosis (Shi et al, 2008;Sakr, 2010), including Clathrin-Dependent (CDE) and Caveolin-Dependent Endocytosis (CvDE).…”
Section: Introductionmentioning
confidence: 99%